2017
DOI: 10.1063/1.4992787
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of alnico coercivity

Abstract: Micromagnetic simulations of alnico show substantial deviations from Stoner-Wohlfarth behavior due to the unique size and spatial distribution of the rod-like Fe-Co phase formed during spinodal decomposition in an external magnetic field. The maximum coercivity is limited by single-rod effects, especially deviations from ellipsoidal shape, and by interactions between the rods. Both the exchange interaction between connected rods and magnetostatic interaction between rods are considered, and the results of our … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…The difference between theoretically achievable coercivity and experimentally measured values is explained by the diameter of the α 1 phase being much larger than the optimal diameter of the magnetic nano-rods assuming a coherent rotation (2R coh = 12.8 nm) mechanism used in the micromagnetic modeling. [9,26] In situ magnetization in TEM showed that the α 1 rods connected by branches tend reverse at the same external magnetic field, this confirms the modeling that branching segments act as short circuits to domain rotation and allow for a cascading domain reversal at lower applied fields. [26] The EDS mapping clearly shows that the Cu-enriched rods extending along the rod boundaries and in some cases providing additional separation (Fig.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The difference between theoretically achievable coercivity and experimentally measured values is explained by the diameter of the α 1 phase being much larger than the optimal diameter of the magnetic nano-rods assuming a coherent rotation (2R coh = 12.8 nm) mechanism used in the micromagnetic modeling. [9,26] In situ magnetization in TEM showed that the α 1 rods connected by branches tend reverse at the same external magnetic field, this confirms the modeling that branching segments act as short circuits to domain rotation and allow for a cascading domain reversal at lower applied fields. [26] The EDS mapping clearly shows that the Cu-enriched rods extending along the rod boundaries and in some cases providing additional separation (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…[9,26] In situ magnetization in TEM showed that the α 1 rods connected by branches tend reverse at the same external magnetic field, this confirms the modeling that branching segments act as short circuits to domain rotation and allow for a cascading domain reversal at lower applied fields. [26] The EDS mapping clearly shows that the Cu-enriched rods extending along the rod boundaries and in some cases providing additional separation (Fig. 3).…”
Section: Discussionsupporting
confidence: 66%
“…The Cu lattice shearing from the bcc structure may be because the fcc structure of Cu is thermodynamically more stable. Moreover, since some branching types may be very detrimental to H ci , a larger Cu cluster can isolate two originally connected α 1 rods and increases H ci [20]. Finally, formation of small α 1 rods or even chains of spheres, along with the previously reported formation of Ni-rich (α 3 ) separation phase at the α 1 / α 2 interface can also help to increase H ci [21].…”
Section: Discussionmentioning
confidence: 91%
“…Any alteration of the spinodal decomposition phenomena during the MA and the concentration of the diffusing species during the lower temperature draw cycles will ultimately impact the magnetic properties. The loss of both Al and Cu was likely a contributor to the observed drop in coercivity as both elements act to separate the Fe-Co rods in the nanostructure; without a high enough concentration of Al and Cu, the Fe-Co rods will no longer be substantially isolated and the coercivity will decrease due to magnetic spin coupling between them [11,12,34,35].…”
Section: Discussionmentioning
confidence: 99%